Complementarity and genetic algorithms for an optimization shell problem - Figueiredo, Isabel N. (2000)
The application of complementarity and genetic algorithms to an optimization thin laminated shallow shell problem is discussed. The discrete form of the problem leads to a Mathematical Program with Equilibrium Constraints (MPEC) [1], whose constraint set consists of a variational inequality and a set of equality constraints. Furthermore the variables are discrete. Special instances of the general problem are considered and indicate that the choice of the algorithm depends on the problem to be linear or nonlinear.